The Influence of Health Education About Delivery on Primigravidal Anxiety Trimester III During the Covid-19 Pandemic in Aek Haruaya Village - Ramadhani Nainggolan (PT Inovasi Pratama Internasional, 2022)
The first delivery for a mother (primigravida) is one of the crisis in his life. On First childbirth often arises anxiety approaching labor mothers with primigravida. Mother pregnant which experience worry During pregnancy will increase risk imbalance mother's emotions after giving birth. Anxiety that occurs continuously in pregnant women have an impact on the baby and pregnant women such as placental abruption, weight low birth weight, the risk of delays in fetal motor and mental development, colic on baby new born and prematurity. Study this aim for determine the effect of providing health education about childbirth on third trimester primigravida anxiety. This quasi-experimental research uses pre and post test method without control with purposive sampling technique conducted on 17 mother pregnant primigravida trimester III in Aek Haruaya Village, Portibi District, North Padang Lawas Regency in 2022. Anxiety was measured using the HARS (Hamilton Anxiety Rating Scale) questionnaire. The results showed that there was a decrease in anxiety scores between before and after treatment ( p = 0.000). So that could concluded that gift health education about childbirth with the lecture method can reduce Anxiety of third trimester primigravida pregnant women in the face of childbirth.